P wave dispersion in patients with hypochondriasis - Atmaca, Murad; Korkmaz, Hasan; Korkmaz, Sevda (Elsevier Ireland Ltd, 2010)
P wave dispersion (Pd), defined as the difference between the maximum and the minimum P wave duration, has been associated with anxiety. Thus, we wondered whether Pd in hypochondriasis which is associated with anxiety differed from that in healthy controls. Pd was measured in 30 hypochondriac patients and same number of physically and mentally healthy age- and gender-matched controls. Hamilton Depression Rating (HDRS) and Hamilton Anxiety Rating Scales (HARS) were scored. The heart rate and left atrium (LA) sizes were not significantly different between groups. However, both Pmax and Pmin values of the patients were significantly higher than those of healthy controls. As for the main variable investigated in the present study, the corrected Pd was significantly longer in the patient group compared to control group. On the basis of this study, we can conclude that Pd may be related to hypochondriasis though our sample is too small to allow us to obtain a clear conclusion. Future studies with larger sample evaluating the effects of treatment are required. (C) 2010 Elsevier Ireland Ltd. All rights reserved.
Keywords: P wave dispersion; Hypochondriasis; Anxiety; Pmax; Pmin